Risiko Ergonomi Pekerja Perkantoran di Rumah Sakit X - Pratiwi, Tiara Amanda; Rosidati, Catur (Journal of Religion and Public Health, 2024)
Poor working posture and non-ergonomic chairs for office workers have the potential to cause ergonomic hazards. This research aims to identify complaints and the level of ergonomic risk among office workers in the medical administration department of the X Hospital. The research used observation and interview methods on 10 respondents using the Nordic Body Map (NBM) and the Rapid Office Strain Assessment analysis technique. (ROSA). Based on the research results, workers with adjustable and non-adjustable chairs reportedsignificant pain in the upper neck, lower neck, waist, and buttocks. Additional complaints were noted by workers using non-adjustable chairs, including considerable pain in the left shoulder, right shoulder, left calf, and right calf. A high level of ergonomic risk was found among workers using non-adjustable chairs with a score of 6. The lowest level of risk was found among workers using adjustable chairs with a score of 3. To reduce ergonomic complaints and lower ergonomic risk, it is necessary to designchairs and desks that match body posture, provide training on the correct use of office equipment, implement regular ergonomic assessments, and provide office facilities that support health.Keywords: Ergonomic, Office workers, Rapid Office Strain Assessment (ROSA)